Implementasi Model Prototype dalam Perancangan Media Edukasi Pencegahan Stunting - Ramadani, Niska; Andeswari, Desi; Farady Coastera, Funny (Akademi Perekam dan Informasi Kesehatan Imelda, 2025)
Stunting can have an impact on child development, therefore comprehensive efforts are needed, one of which is through educational media. Stunting in Indonesia is still a significant public health problem, lack of parental understanding of good nutrition is part of the cause of stunting. In the development of Information Technology, it has a role in stunting prevention efforts, both in terms of monitoring, education, and data-based decision making. The purpose of this research is to create educational media that can be used as a learning tool and increase the understanding of mothers and prospective mothers about stunting. This application is built on the Android platform and can function using the Internet of Things (IoT) concept. This research applies a prototyping method that is developed based on user needs, as well as a mobile interface guidelines approach to guide the design of user interfaces that are tailored to target users. Based on the results of the research, an educational media design on stunting prevention has been created. The Android-based stunting prevention education application is designed to provide easily accessible, interactive and personalised information on the importance of balanced nutrition, a healthy diet and environmental hygiene. The app provides features such as exclusive breastfeeding guidelines, information on nutritious foods, health care tips for pregnant women and toddlers, and educational quizzes.